Theoretical contributions for the conceptualization of Henri Lefebvre’s spaces of representation - Castro-Martínez, Enrique de Jesús (2021)
Spaces of representation comprise a dimension of the unitary theory of the production of space proposed by Henri Lefebvre and responds to multiple interpretations in view of its polyvalent and polysemic character.  For this reason, we propose three explanations that cast symbols as interpretations of the spaces of representation. First in mention are natural symbols which were subsequently appropriated by the exercise of power, religion and political forces; second, everyday life symbols, which respond to the advent of modernity, dominated by technique and the rise of capitalism; and thirdly, counter-space, which promotes urban resistance to provide the recovery of collectivities produced by living spaces.